Group psychedelic therapy: empirical estimates of cost-savings and improved access - Marseille, Elliot; Stauffer, Christopher S.; Agrawal, Manish; Thambi, Paul; Roddy, Kimberly; Mithoefer, Michael; Bertozzi, Stefano M.; Kahn, James G. (Frontiers in Psychiatry, 2023)
Objective: To compare group and individual psychedelic-assisted therapy in terms of clinician time, costs and patient access.Methods: Using 2023 data from two group therapy trial sites, one using 3,4-Methylenedioxy methamphetamine (MDMA) to treat posttraumatic stress disorder (PTSD), and one using psilocybin to treat major depressive disorder (MDD), we compared overall variable costs, clinician costs and clinician time required by therapy protocols utilizing groups versus individual patient therapy. Using published literature, we estimated the prevalence of adults with PTSD and MDD eligible for treatment with psychedelic therapy and projected the savings in time and cost required to treat these prevalent cases.